Perundingan Bipartit pada Industri Alas Kaki Mengenai Kenaikan Upah Minimum Kota Tangerang (Studi pada Dua Perusahaan Alas Kaki di Kota Tangerang) - Irvan Sebastian Iskandar; Fitriyah .; Achmad Taufiq (Journal of Politic and Government Studies, 2015)
This research discussed about how conflict seetlement beetwen employers and labours caused by the minimum wages increasement in Tangerang Municipality which was applied to all footwear industries, as labour intensive manufacture industry, finished through a bipartite negotiation process from companies decentralization trusted by goverment as a first procedure in industrial conflict resolution. The samples taken from two footwear companies in Tangerang. The researched used qualitative method to understand and describe not only how bipartite negotiation proceed and also know what are the consequences. The result had showed that there were differencies beetwen two companies on bipartite negotiaton had to do according their companies form and condition. Although reaching a mutual agreement beetwen the two parties. Actually the labours were in a very weak position, because the consequences such as contract structure and working hour which they got, was designed only by one side the employers without passing over the proposal of those working changing to the labours. More over it didn’t discuss in bipartite negotiation in the same way as they discussed about the raising minimum wages. The management main interest were to cover the profit deficit, to cover that production cost (unit labour cost) with labours productivity and the wages cost which depend on the labours educational background. The main workers interest was a job security.Key words: Industrial relation, Manpower Supervision, Labour.